Analisis Pendapatan Usaha Pada Proses Budidaya Udang Vanammei (Lithoppenaeus Vannamei ) Pada Tambak Intensif di CV. Kurnia Tirta Makmur Probolinggo Jawa Timur - Nur Hidayat; Karma Karma; Abdullah Abdullah (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2024)
Production is the activity of producing goods or services. Usually this activity is carried out in order to add value to the use or benefits of goods and services. The aim of this research is to determine the costs and revenues of vannamei shrimp cultivation in intensive ponds in CV. Kurnia Tirta Makmur. The research method used was purposive sampling. Data collection is divided into two types, namely primary data collection and secondary data collection. This research uses one data analysis, namely income analysis. Based on the Analysis of Business Income in the Cultivation Process of Vanammei Shrimp (Lithoppenaeus Vannamei) in Intensive Ponds at Cv. Kurnia Tirta Makmur Fixed Costs for the Vannamei Shrimp Farming Business are IDR. 286,271,456, Variable Costs for the Vannamei Shrimp Farming Business amounting to Rp. 1,170,903,367, Vannamei Shrimp Farm Business Costs of Rp. 1,457,174,823, Revenue from Vannamei Shrimp Farming Business amounting to Rp. 3,027,403,731, Vannamei Shrimp Farming Business Income of Rp. 1,552,228,907.